David versus goliath: ACE2-Fc receptor traps as potential SARS-CoV-2 inhibitors - Alfaleh, Mohamed A.; Zawawi, Ayat; Al-Amri, Sawsan S.; Hashem, Anwar M. (mAbs, 2022)
Anti-SARS-CoV-2 monoclonal antibodies and vaccines have shown improvement in lowering viral burden and hospitalization. However, emerging SARS-CoV-2 variants contain neutralizing antibody-escape mutations. Therefore, several reports have suggested the administration of recombinant angiotensin-converting enzyme 2 (rACE2) as a soluble receptor trap to block SARS-CoV-2 infection and limit viral escape potential. Several strategies have been implemented to enhance the efficacy of rACE2 as a therapeutic agent. Fc fusions have been used to improve pharmacokinetics and boost the affinity and avidity of ACE2 decoys for the virus spike protein. Furthermore, the intrinsic catalytic activity of ACE2 can be eliminated by introducing point mutations on the catalytic site of ACE2 to obtain an exclusive antiviral activity. This review summarizes different evolution platforms that have been used to enhance ACE2-Fc (i.e., immunoadhesins) as potential therapeutics for the current pandemic or future outbreaks of SARS-associated betacoronaviruses.